Surfactant-cosurfactant interactions and process parameters involved in the formulation of stable and small droplet-sized benznidazole-loaded soybean O/W emulsions - Streck, Leticia; Araujo, Margarete M. de; Souza, Izadora de; Fernandes-Pedrosa, Matheus F.; Egito, Eryvaldo Socrates T. do; Oliveira, Anselmo Gomes de [UNESP]; Silva-Junior, Arnobio A. da (Elsevier B.V., 2014)
The ability of different surfactant mixtures (SM) (polysorbate 80/sorbitan monooleate, 5 to 10% w/w) with cosurfactants (CO) (benzyl alcohol, ethanol, and 2-methylpyrrolidone) to produce stable benznidazole (BNZ) loaded soybean oil (SO, 10 to 30% w/w) in water (O/tW) emulsions was well assessed. Statistical tests were performed to select the best procedure parameters (temperature, shake conditions, and order inversion phases), using a phase inversion technique (PIT). Phase behavior was assessed by the pseudo-ternary phase diagram at the best HLB (9.0). Physicochemical stability was assessed at different storage conditions (4 degrees C, 25 degrees C, and 45 degrees C, with thermal stress of 24 h at each temperature, 30 days). Rheological measurements demonstrated that all SO emulsions exhibited pseudoplastic flow-type (n-0.5) liquid-like behavior (k-0.19) with the absence of storage modulus (G') and a predominance of loss modulus (G '') even for the most concentrated emulsion (30% w/w SO), and confirmed stability regarding flocculation. The droplet size remained between 42 and 61 nm (PDI inferior to 03). However, benzyl alcohol contributed to an increase in droplet size, while 2-methylpyrrolidone led to the smallest droplet size. BNZ showed a weak interaction with the oil phase, but stable SO in water emulsions was produced with small and uniform droplet size containing a soluble drug fraction about four times greater than its aqueous solubility. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Emulsion; Soybean oil; Benznidazole; Physical stability; Rheology; Colloidal drug delivery systems